2000
DOI: 10.1017/s0007114500001379
|View full text |Cite
|
Sign up to set email alerts
|

Response of putative indices of copper status to copper supplementation in human subjects

Abstract: No sensitive functional index is currently available to assess Cu status in healthy human populations. This study evaluated the effect of Cu supplementation on putative indices of Cu status in twelve women and twelve men, aged between 22 and 45 years, who participated in a double-blind placebo controlled crossover study. The study consisted of three 6-week supplementation regimens of 3 mg CuSO4, 3 mg Cu-glycine chelate and 6 mg Cu-glycine chelate, each separated by placebo periods of equal length. Women had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…In contrast, Dorton et al (2003) reported no difference in RBC SOD activity for control and steers supplemented with 10 or 20 mg Cu/kg DM from organic or inorganic source. This enzyme also has been shown to be unresponsive to Cu supplementation compared to diamine oxidase activity in Cu status assessment study on human subjects (Kehoe et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Dorton et al (2003) reported no difference in RBC SOD activity for control and steers supplemented with 10 or 20 mg Cu/kg DM from organic or inorganic source. This enzyme also has been shown to be unresponsive to Cu supplementation compared to diamine oxidase activity in Cu status assessment study on human subjects (Kehoe et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…One might expect that the earliest effects of copper exposure are of lesser intensity; therefore, it is most relevant that the traditional indicators measured in blood to assess copper status, liver function, and oxidative stress vary as described here in relation to the estradiol/progesterone blood concentrations. Identifying blood predictors of biologically relevant changes in copper status has proved to be difficult [2,4,5,7]; the influence of uncontrolled factors such as the hormones evaluated here may be part of the explanation. Cellular studies show that estradiols increase both copper transporters (mRNA and protein) and hence cell copper uptake; since copper favors cell proliferation and differentiation [32], the increase of copper derived from the presence of estrogen would help in improving cell copper bioavailability for metabolic needs, including those related to cell growth, proliferation, and reproduction [33,40].…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, several investigations explored the magnitude and duration of excess copper intake necessary to induce detectable effects in apparently healthy individuals. In these studies, blood indicators have repeatedly failed to detect significant changes in adult women and men exposed to a range of copper dosing [1][2][3][4][5]; yet, principal component analysis and linear discriminant analysis showed that the variable most closely associated with the results observed was the participant's sex [6]. Women developed significantly more adverse effects after acute exposure to copper [7,8], but no differences have been demonstrated when copper exposure is for longer periods [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to lack of sensitive markers able to detect them. Efforts to identify sensitive and specific responses at whole body, blood biochemistry, or cellular levels have yielded unsatisfactory results [1,2]. Only rather intense alterations of copper metabolism like in Menkes syndrome, Wilson disease, and hepatitis can be diagnosed by measuring plasma copper concentration and ceruloplasmin [3,4]; otherwise, blood biochemical indicators are not sensitive indicators.…”
Section: Introductionmentioning
confidence: 99%